2022
DOI: 10.3390/buildings12071005
|View full text |Cite
|
Sign up to set email alerts
|

No More Illegal Subdivided Units? A Game-Theoretical Explanation of the Failure of Building Control in Hong Kong

Abstract: Safety has long been regarded as one of the most important functional requirements of buildings. However, building safety in Hong Kong has long been jeopardised by the proliferation of unauthorised building works (UBWs), which are essentially works constructed without any prior approval or consent of the government. Due to the acute problem of housing supply–demand imbalance, the numbers of illegal subdivided units (ISUs) in the city have been increasing since the early 2010s, frequently resulting in injuries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 64 publications
(97 reference statements)
0
2
0
Order By: Relevance
“…The living environment and quality of life showed substantial improvement. Since many TSH residents were reallocated from SDUs, the results showed that TSH is a critical housing project for improving the housing circumstances of SDU residents facing problems of small living areas and high rent [8,14].…”
Section: Significant Improvement In Housing Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The living environment and quality of life showed substantial improvement. Since many TSH residents were reallocated from SDUs, the results showed that TSH is a critical housing project for improving the housing circumstances of SDU residents facing problems of small living areas and high rent [8,14].…”
Section: Significant Improvement In Housing Conditionsmentioning
confidence: 99%
“…SDU residents face various substandard living conditions, which seriously influence their well-being. The damaged building structures of SDUs threaten fire safety [14]. Extra plumbing fixtures installed by landlords may lead to water seepage, which can cause property damage or create dangerous moulds for tenants [15].…”
Section: Introduction 1grassroots Housing Conditions In Hong Kongmentioning
confidence: 99%